Ordbok över finska dialekter och evigheten - Vilppula, Matti (Nordiske Studier i Leksikografi, 1997)
The Dictionary ofFinnish Dialects is planned to comprise 20 volumes, five ofwhich have been finished. The remaining 15 volumes will be published in about 30 years to come. The dictionary describes the language forms spoken in the Finnish countryside, in different counties and parishes, about hundred years ago. The article discusses the problems caused by the fact that the language and culture to be described belong to the past, and that it will take tens of years until the dictionary is finished. Additionally, the future users ofthe dictionary have not yet been bom. Are the editors ofthe dictionary able to fully understand the world and way ofthinking of the people who lived hundred years ago, and are they able to explain that world in such a way that even those who will live many generations afl:er us, will understand it?